Manifestation of Investments in the Economy of Uzbekistan - Bobomurotova Manzura Panji qizi (Zien Journals, 2022)
in this article, it is learned that the rational regulation of foreign economic activity in the economic development of our country is an important component of the state strategy, one of its main directions is the attraction of foreign investments to the Republic. The work carried out to attract foreign investment, the investments made by international financial institutions, the efforts of the country to gain its place in World Trade were analyzed.
Keywords: economic reforms; foreign economic activity; foreign investment; foreign direct investment